Spiritual Harmony: Dynamics of Religiosity and Forgiveness in Adolescents After Parental Divorce - Oktaviany, Irine (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
This research aims to determine the relationship between religiosity and forgiveness in adolescents with divorced parents. This research uses quantitative methods to achieve research objectives. The research subjects used in this study were teenagers aged 18 – 22 years whose parents had divorced within the last 5 years. This research uses a non-probability sampling technique, namely purposive sampling. The measuring instrument used in this research was the forgiveness and religiosity scale with research subjects of 62 teenagers with divorced parents. The research data in this study was analyzed using the Pearson Product Moment correlation test. The results of research from the data analysis that has been carried out show that the Pearson Product Moment correlation coefficient is 0.756 with a level of p = 0.000 < 0.01, which means that there is a significant positive relationship between religiosity and forgiveness in teenagers with divorced parents. From the results of this research, it can be concluded that the higher the level of religiosity in teenagers, the higher the forgiveness of teenagers with divorced parents. Conversely, the lower the level of religiosity in adolescents, the lower the forgiveness of adolescents with divorced parents. Keywords: Religiosity, Forgiveness, Adolescents, Divorced, Parents